A participatory study of the interplay between gender, social dynamics and food security in a South African township - Canca, Nombqophiso Monica (Rhodes University, 2026)
This participatory study investigates the interplay between gender, social dynamics, and food security in an informal settlement in Makhanda, Eastern Cape, South Africa. The study seeks to surface and investigate these connected factors, looking at how they influence each other, with a particular focus on gender roles and the social context within which these interactions unfold. The research highlights the disproportionate vulnerability of African women in food-insecure contexts due to traditional caregiving roles, exacerbated by socioeconomic and political challenges. The study examines how gender roles and community dynamics influence responses to food insecurity, with a focus on collaborative learning opportunities for sustainable solutions. The study investigates the impacts of food insecurity at different levels within the community, focusing on community-level experiences and household experiences. Situated in a country like South Africa, with its history of apartheid, and still steeped in inequalities and injustices which remain unaddressed 30 years into democracy, the transition to a free and fair society has been difficult to translate into practice. This is despite what is lauded as one of the best constitutions in the world. The study demonstrates that food security cannot be separated from broader socio-political issues that affect individuals and communities. The study approaches food insecurity as more than a state of lacking food for consumption, but rather a complete disempowerment of a people through economic, social and political exclusion. Poverty, unemployment and densely populated informal settlements have become fertile ground for exacerbated food insecurity in a country where unemployment has reached alarming heights. This study is undertaken in an informal settlement with the purpose of bringing in the voices from the margins to a conversation that is necessary for future generations to not only exist but thrive, together, as South Africans, beyond race, class or gender divides. Adopting a Community Based Participatory Research (CBPR) approach, the study integrates Africana Womanist and Intersectional theories alongside uBuntu ethical praxis to frame the lived experiences of marginalised communities. Data collection methods included dialogues, focus groups, and gender daily calendars, enabling nuanced exploration of household and community-level food insecurity. Findings revealed that there is a need for gender-sensitive and context-specific interventions that promote collective action and leverage Indigenous knowledge systems. Through situating food insecurity within broader socio-political inequalities, the study advocates for empowering communities to co-create solutions that transcend race, class, and gender divides, fostering resilience and equity in the fight against hunger. Throughout the study, there was a continuous thread of community learning for all involved. This included me as the researcher and the community partners in equal measure. The participatory nature of the study required contribution from all participants, in the form of knowledge and skills sharing. While I brought in a certain level of theoretical framing, the community partners brought in knowledge of the community and an understanding of what would work best for them given their circumstances. It positioned research not just as a form of knowledge production but as co-created knowledge for actionable community change. The process itself was a learning experience, with lessons on navigating relationships, approaching the research process as a mutually beneficial partnership for all involved as well as the importance of transparency in establishing community–university partnerships. This boded well for developing a conducive learning environment and set the tone for cooperation and active participation for all.
Keywords: Vulnerability; Food security; Social dynamics; Participant observation; Participatory research